The history learning module integrated character values - Jems Sopacua; Muhammad Rijal Fadli; Saefur Rochmat (Intelektual Pustaka Media Utama, 2020)
The history learning module integrated character values is an innovation in history learning in schools to support educational progress. This module serves as teaching material for the process of character formation of students obtained through independent learning to achieve the desired competency goals. This research uses the development (R and D) of the 4D model (define, design, development and dissemination). The results showed that the module was declared feasible based on the results of the validation of the experts, so the modules that had been developed were feasible, effective and practical to be used as teaching materials and learning resources by students in the history learning process. This module has the advantage that there are character values (love of the motherland, curiosity, religious and tolerance) in the material presented for the formation of students' character.